KOMPARASI MOTIVASI BELAJAR SISWA ANTARA METODE PEMBELAJARAN CERAMAH DENGAN METODE PEMBELAJARAN TANYA JAWAB PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 1 NAN SABARIS - Deny Hamzah (JURNAL BUANA, 2021)
The Purpose of this study was to determine the significant differences in student motivation between the use of the lecture method and the question and answer methode in learning Geography at SMA Negeri 1 Nan Sabaris. This type of reasearh is an experiment, with the reasearch was conducted at SMA Negeri 1 Nan Sabaris. The research hypothesis was tested by using the t-test at the level of 0.05 and dk= 68, before using the t-test, the prerequisite analysisi was carriwd out, namely the normality and homogenity tests. Based on the results of the anlysis of the averege score of student learning motivation in Geography learning who learns using the quistion and anser method namely 3.9 with a good category. Meanwhile, the averege score of student learning motivation using the lecture learning methode is 3.4 in the moderate category. From the results of t-test aanalysis obtained t-count>t table (3.07>1.49) at a significant level of 0.05. it turns out that proposed hypothesis is acecepted (H1 is accepted, H0 is rejected)